Study the Level of Awareness Among Housewives About Environmental Education - Muhammad Latif Javed; Rashid Ahmad; Muhammad Nadeem Javed; Muhammad Umar (Journal of Business and Social Review in Emerging Economies, 2019)
The purpose of this paper was to study the level of awareness among housewives about environmental education. For this task review of existing literature was carried out. Being descriptive study, survey method was adopted for data collection. A group of 50 housewives from Bahawalnagar District of Division Bahawalpur was recognized as sample to accomplish the study. Closed ended questionnaire for housewives were developed on Likert scale and data was collected. Data collected through questionnaire was tabulated, analysis and discussed. The analysis was arranged on the basis of respondents and the housewives’ opinions were analyzed. The result from the findings of this study showed that active learning of the housewives has appeared with the expansion of their actions in the Green Future. With the presence at the Eco conductors Training course as an opening, they come to join in the Eco conducting Activity and developed Green Future into an essential association connected to the eco-environment in the society. Their Eco-conducting movement was based on the outcome of knowledge from the teaching courses, in which the accessible expert in Eco conducting skilled them. At the end some recommendations were made to improve housewives’ skills and awareness about environmental education.